2016
DOI: 10.1371/journal.pone.0158899
|View full text |Cite
|
Sign up to set email alerts
|

Illumina Sequencing Reveals Aberrant Expression of MicroRNAs and Their Variants in Whitefish (Coregonus lavaretus) Liver after Exposure to Microcystin-LR

Abstract: Molecular analyses show that challenging fish with microcystin-LR (MC-LR) causes perturbations of microRNA (miRNA) signaling. However, the significance and scope of these alterations is currently unknown. To address this issue, we studied miRNA gene expression in the liver of juvenile whitefish, C. lavaretus, during 28 days of exposure to a subacute dose of MC-LR (100 μg·kg-1 body mass). Using genomic resources of Atlantic salmon (AGKD03), the mature miRNA library of Atlantic salmon (miRBase-21) and bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…Our previous results showed that repeated exposure of white sh to MC-LR results in severe liver damage, followed by an unexpected resilience to further exposures to the toxin and regeneration of the damaged liver structure [14]. We showed that in these adaptations, MC-LR regulates several hepatic miRNA signaling pathways and alters the expression pro les of miRNAs over the short-term [15] and long-term [16], suggesting extensive transcriptome rebuilding during these processes. Because lncRNAs have been implicated in species-speci c adaptations (e.g.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our previous results showed that repeated exposure of white sh to MC-LR results in severe liver damage, followed by an unexpected resilience to further exposures to the toxin and regeneration of the damaged liver structure [14]. We showed that in these adaptations, MC-LR regulates several hepatic miRNA signaling pathways and alters the expression pro les of miRNAs over the short-term [15] and long-term [16], suggesting extensive transcriptome rebuilding during these processes. Because lncRNAs have been implicated in species-speci c adaptations (e.g.…”
Section: Introductionmentioning
confidence: 75%
“…The dose of MC-LR (100 μg•kg -1 of body mass) and the treatment periods (1, 6, and 9 days) were based on our previous studies on molecular and physiological responses of white sh to this toxin [14,16,21]. MC-LR (purity ≥ 95%; HPLC) was obtained from Enzo Life Sciences (Enzo Biochem, Inc.; USA) and dissolved in phosphate buffer saline (PBS) as a solvent vehicle.…”
Section: Fish Maintenance and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The miRNA study performed on whitefish (Coregonus lavaretus) revealed that exposure to microcystin-LR results in perturbation on hepatic miRNA signaling pathway. The results concluded that miRNA and its variants can be used as markers for identification of liver-specific diseases in mammals [9]. Some miRNA and target genes, which are associated with human diseases are also well conserved in domestic animals.…”
Section: Panther Classification Of Mirna-target Gene Productsmentioning
confidence: 92%
“…The isomiRs, i.e. the sequence variants of known miR-NAs, are gaining importance in human, rat, mice and other species for their putative role in various diseases [9][10][11]. It is sometimes evident that the canonical sequence of miRNAs encoded by the same gene displays variation in length and sequence because of addition/ deletion of one or more bases at any one or both the termini [12].…”
Section: Introductionmentioning
confidence: 99%